(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This paper brings to the fore techniques for proper management of saline water intrusion in coastal region because of the hardship its negligence bring upon the public that rely on it for livelihood. Groundwater remains the main source of quality and adequate water supply in the world over from which we get water for domestic, agricultural and industrial usage. One of the factors affecting the quality of water from this source is saline water intrusion, especially in coastal aquifers. This problem affects the potability of the water and the population that depends on it. Therefore, due to the aforementioned problem, measures must be put in place in order to adequately manage and control saline water intrusion so as to protect the dependent population from untold hardship that may result in near future.